Perlindungan Hukum Bagi Pemegang Sertifikat HGB Daluarsa: Studi Kasus Nomor 499/PDT.G/2011/PN.JKT.PST) - Nurokhim Nurokhim; Hasbi Hasan; Ismail Rumadhan (Jurnal Penelitian Hukum Legalitas, 2016)
Disputes, conflicts, and land issues never seem to recede, and tend to increase in intensity and diversity, as it becomes increasingly difficult to access land and increase the bargaining position between the three development actors - government, the private sector, and community to acquire land. The type of research is normative research that is analytical descriptive. The data collection technique used is literature study. Legal materials used include (1) the 1945 Constitution, Law No. 5 of 1960, Law No. 40 of 1996, Government Regulation No. 24 of 1997 and; (2) Secondary law materials: Scientific books; Documents; Reports and materials from the internet. Due to the various obstacles experienced by the justice seekers in court in court, it is time to take a relatively simple alternative (non-litigation) dispute resolution, shorter time and lower cost. This model is called Alternative Dispute Resolution (ADR). The familiar forms of ADR in Indonesia include mediation, arbitration, conciliation, and negotiation. Of the various types of ADR, which is more suitable to be applied in the field of land is mediation. This choice is based on consideration because the structure and mechanism are simpler. Besides, for the Indonesian people who uphold the principle of discussion to reach consensus, this institution feels familiar. And lately, the means used by Komnas HAM in resolving various disputes also utilize the principles of mediation